A new primary emanation standard for Radon-222. (February 2020) - Mertes, Florian; Röttger, Stefan; Röttger, Annette
Abstract: New emanation sources for Rn-222 have been developed by electrodeposition of Ra-226 onto stainless-steel discs. With a high resolution of up to 20 keV FWHM in the Ra-226 peak at 4.87 MeV, defined solid-angle alpha-particle spectrometry is the method of choice to determine the deposited Ra-226 activity. The amount of emanating Rn-222 is determined by gamma-ray spectrometry using HPGe-detectors. The measurement is based on the distorted equilibrium of the Ra-226 decay chain due to Rn-222 emanation. Comparative gamma-ray spectrometric measurements with sealed, Rn-222 tight sources of the same type and geometry make the knowledge of emission probabilities and detection efficiency unnecessary. The new emanation sources allow the production of stable reference atmospheres in the regime below 300 Bq ⋅ m −3 with uncertainties not exceeding 2% for k = 1. Highlights: Rn-222 sources based on electrodeposited Ra-226 were produced. Primary emanation standard for Rn-222. Uncertainties do not exceed 2% regarding Rn-222 flow from the sources.